2013
DOI: 10.5051/jpis.2013.43.4.183
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of periodontal pathogens present in the saliva of geriatric subjects

Abstract: PurposeAt present, information regarding periodontal disease in geriatric patients is scarce. The purpose of this study was to quantify the periodontal pathogens present in the saliva of Korean geriatric patients and assess the relationship between the bacterial levels and the periodontal condition.MethodsSix putative periodontal pathogens were quantified by using a real-time polymerase chain reaction assay in geriatric patient groups (>60 years) with mild chronic periodontitis (MCP), moderate chronic periodon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 35 publications
0
20
0
Order By: Relevance
“…This is due to variations in the number of salivary bacteria among the different time points as well as the small proportion of periodontal pathogens (less than 0.02%) relative to total bacteria in saliva. Compared with a previous study that showed a salivary level of periodontal pathogens from 10 4 to 10 7 cells per mL in patients with periodontal disease, 5 most subjects in this study had fewer than 10 4 periodontal pathogens in their saliva. This might be explained by the fact that the subjects in this study practiced relatively good oral hygiene (OHI-S was 1.45 6 0.7 at T1) without any active periodontal lesions.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…This is due to variations in the number of salivary bacteria among the different time points as well as the small proportion of periodontal pathogens (less than 0.02%) relative to total bacteria in saliva. Compared with a previous study that showed a salivary level of periodontal pathogens from 10 4 to 10 7 cells per mL in patients with periodontal disease, 5 most subjects in this study had fewer than 10 4 periodontal pathogens in their saliva. This might be explained by the fact that the subjects in this study practiced relatively good oral hygiene (OHI-S was 1.45 6 0.7 at T1) without any active periodontal lesions.…”
Section: Discussionmentioning
confidence: 69%
“…When power analysis to estimate effect size was performed using information from previous studies, 5,7 at least 40 subjects would have been required to analyze the periodontal pathogens. Because a previous study showed that bracket type does not significantly influence time-related differences in salivary bacterial levels, 9 saliva samples from 54 subjects with different brackets were analyzed as one group to evaluate time-related changes in salivary levels of periodontal pathogens after debonding ( Table 1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The purpose of this study was to assess humoral immune (IgG) responses to periodontal pathogens in elderly patients with chronic periodontitis in an effort to better understand immune function in this group. Serum samples were obtained from the same geriatric patients used in our previous microbiological study [ 16 ], and here we analyzed IgG antibody levels in response to six periodontal pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the present study indicate that serum IgG antibody levels to P. gingivalis , T. forsythia , T. denticola, and F. nucleatum in patients with SCP were higher than in those with MCP. Our previous study showed that the amount of these bacteria increased as the severity of the disease increased from MCP to SCP, and that the presence of these bacteria in the saliva was associated with the severity of periodontal disease in geriatric patients [ 16 ]. Considering the fact that IgG levels may reflect a host’s previous exposure to periodontal pathogens [ 8 ], the present results suggest that increased IgG levels reflect the current disease status of chronic periodontitis.…”
Section: Discussionmentioning
confidence: 99%